PERSEPSI PEMILIH PEMULA DI DESA SUNGAI PINANG TERHADAP PEMILIHAN KEPALA DAERAH (PILKADA) KUANTAN SINGINGI TAHUN 2020 - Desi Murni; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the occurrence of various problems during the election of regional heads both at the preparation stage and at the stage of holding the elections in Kuantan Singingi Regency. The formulation of the problem in this study is how are the perceptions of the beginner voters in Sungai Pinang Village towards the 2020 Kuantan Singingi Regional Head Election. The purpose of this study is to determine the perceptions of the beginner voters in Sungai Pinang Village towards the 2020 Kuantan Singingi Regional Head Election. The research method used is descriptive quantitative. The data collection instruments used in this study were questionnaires and interviews consisting of 20 questions with 2 indicators. The population in this study is the Beginner Voters in Sungai Pinang Village, amounting to 66 people. The sample in this study was the entire population, namely Beginner Voters in Sungai Pinang Village, amounting 66 people. Based on the results of the study, it was found that the average percentage value of the dominant respondent’s alternative answers was 84,3%, where this range was in the “Good” category with an existence in the range of 51%-100%. Thus, it can be concluded that the perception of beginner voters in Sungai Pinang Village towards the 2020 Kuantan Singingi Regional Head Election (Pilkada) is in the “Good” category.Key Words: Perception, Beginner Voter, Pilkada.